COMMUNICATION STRATEGIES OF SMALL BUSINESS IN THE CONTEXT OF MEDIATISATION (UKRAINIAN CASES OF THE MARTIAL LAW PERIOD) - Tetiana Ivaniukha; Anastasiia Zelinska; Ihor Darmostuk (Baltic Journal of Economic Studies)
In the context of martial law, modern business in Ukraine requires the development and constant updating of effective strategies to support small enterprises. This article examines the role of information and communication tools in the context of mediatisation, digitalisation, and socio-political challenges. The study aims to identify and analyse the communication strategies and external communication tools used by small enterprises during martial law. To achieve this, the study focuses on small restaurant businesses, specifically coffee houses in Zaporizhzhia, Ukraine, in times of uncertainty. The paper conducts a discourse analysis of communication practices of Ukrainian small enterprises, a case study of Zaporizhzhia coffee houses, a comparative analysis to compare the information and communication activities of these enterprises, and uses methods of classification and systematisation. The scientific novelty of the results obtained is that the paper proposes a systematisation of the views of European scholars on communication tools for supporting small businesses. Research on information and communication tools for supporting small businesses during martial law has the potential to contribute to the preservation and support of small enterprises. Furthermore, such research can also help to establish work, speed up work processes, reduce costs and preserve jobs in difficult conditions of military conflict. The results of the study can be used to substantiate political and economic decisions to support small businesses during martial law. The analysis of the impact of information and communication tools, and the development of strategies for their utilisation, can serve as the foundation for the creation of programmes, thereby playing a pivotal role in the support and regulation of small businesses. It has been determined that a detailed study in this area can contribute to the development of new innovative solutions and improve the effectiveness of support for enterprises in wartime. It is evident that small businesses play a pivotal role in the economic development and job creation of a nation. The effective operation of these enterprises has a considerable impact on the state's economy, contributing to the development of employment opportunities in the field of information and communication technologies.